Technostress - Hatice Fatoş Gür Akınoğlu (Türk Kütüphaneciliği)
This report gives the sources and reasons for TECHNOSTRESS which affects personnel, users and managers in libraries, documentation and information centres of Turkey. Recommendations are made to the managers of these Centres, based on the author’s personal obsenations and the results of the interviews with centre staff. Sources of TECHNOSTRESS m libraries in Turkey are presented as Annexes together with some additional information obtained from the audience of a conference on the subject.